2020
DOI: 10.34172/jcvtr.2020.54
|View full text |Cite
|
Sign up to set email alerts
|

Acute right upper extremity ischemia resulting from true aneurysmof right brachial artery: A case report

Abstract: We report a case of 66-year-old woman with true aneurysm of the right brachial artery. She presented with acute upper extremity ischemia. The hand was cold and parenthesized and distal pulses were absent. CT angiography (CTA) revealed a 20*25 mm true brachial artery aneurysm. The aneurysm was thrombosed without distal run-off. We excised the aneurysm and reestablished the arterial flow by a reverse saphenous interposition graft. The postoperative course was uneventful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hall et al [ 7 ] mentioned that nonsurgical treatment can be considered when the aneurysm is small and asymptomatic; however, they also established that surgical repair is the best option. In contrast, Tadayon et al [ 13 ] proposed open surgery with autogenous vein graft as the treatment of choice. Senarslan et al [ 14 ] reported that endovascular techniques are a viable management option.…”
Section: Discussionmentioning
confidence: 99%
“…Hall et al [ 7 ] mentioned that nonsurgical treatment can be considered when the aneurysm is small and asymptomatic; however, they also established that surgical repair is the best option. In contrast, Tadayon et al [ 13 ] proposed open surgery with autogenous vein graft as the treatment of choice. Senarslan et al [ 14 ] reported that endovascular techniques are a viable management option.…”
Section: Discussionmentioning
confidence: 99%
“…Bypass with greater saphenous vein interposition graft has been the most frequently employed treatment. 2,3,[23][24][25][26][27] We decided to use the right great saphenous vein in this patient, because it was the largest conduit available. The cephalic vein 14 or the basilic vein 28 have also been used with the theoretical advantage of avoiding an incision in lower extremity and preserving the saphenous vein for possible future vascular reconstructions.…”
Section: Discussionmentioning
confidence: 99%